2016
DOI: 10.1177/1947603515623992
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Implants

Abstract: Objective. To compare the regenerative capacity of 2 distinct bilayer implants for the restoration of osteochondral defects in a preliminary sheep model. Methods. Critical sized osteochondral defects were treated with a novel biomimetic poly-ε-caprolactone (PCL) implant (Treatment No. 2; n = 6) or a combination of Chondro-Gide and Orthoss (Treatment No. 1; n = 6). At 19 months postoperation, repair tissue (n = 5 each) was analyzed for histology and biochemistry. Electromechanical mappings (Arthro-BST) were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…It has recently been shown that electromechanical assessment of cartilage quality after implantation of bilayer constructs was comparable with evaluation by conventional destructive methods in an in vivo sheep model. 15 Similarly, measurement of cartilage electromechanical properties during routine arthroscopic procedures can help to evaluate the tissue quality before major macroscopic lesions appear. Advantages and limitations of the described technique are discussed in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that electromechanical assessment of cartilage quality after implantation of bilayer constructs was comparable with evaluation by conventional destructive methods in an in vivo sheep model. 15 Similarly, measurement of cartilage electromechanical properties during routine arthroscopic procedures can help to evaluate the tissue quality before major macroscopic lesions appear. Advantages and limitations of the described technique are discussed in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogels are categorized as natural and synthetic and can be modulated with cell-free or cell-laden scaffolds. Some of the cell-free scaffolds have been presented with the use of bacterial nano-cellulose [ 102 ], polyethylene glycol (PEG) in combination with HA [ 103 ], collagen-hydroxyapatite hybrids [ 104 ], aragonite-hyaluronate membranes [ 105 ], acrylamide (AAm) hydrogels [ 106 ], alginate (Alg)/chitosan compounds, agarose/polyglycolic acids (PGA) [ 107 ], and porous polycaprolactone (PCL) [ 108 ]. The mentioned scaffolds were used clinically; however, after clinical follow-up in the longer term, they were rejected due to the lack of strength and durability.…”
Section: Tissue Engineering Of Articular Cartilagementioning
confidence: 99%